The Relationships Among Physiological Characters and Productivities of Nine PGL Clones in Medium Land - Ika Irmayanti; Didik Indradewa; Eka Tarwaca Susila Putra (Jurnal Ilmu Pertanian, 2015)
The objectives of the study were to determine the relationships among the physiological characters and productivities of nine PGL clones in medium land. Field trial was arranged in a Randomized Complete Block Design (RCBD) single factor with three blocks as replications. The treatment was PGL clones, consisting of nine clones, namely PGL 1 PGL 3, 4 PGL, PGL 7, PGL 10, PGL 11, PGL 12, PGL 15, and PGL 17. The observations were done on several variables of physiological characters and productivities. Data were analyzed by using the Analysis of Variance (ANOVA) at 5% levels. If there were significant differences among the treatments, they will be analysed by Duncan Multiple Range Test (DMRT). The relationships among variables were determined using correlation analysis. Results showed that there were wide variations in the stomatal density and width openings  and also productivities among the nine PGL clones. Stomatal density and width openings have significant positive correlation with the productivity. PGL 12 and 15 with a denser of stomatal arrangement and wider stomatal openings have higher productivities when compared to other PGL clones, especially PGL 7 with the most loosely stomatal arrangement and narrower stomatal openings.